Design and Implementation of a Cryptographic Framework for Secure Communication Using Audio Steganography in Digital Music - Rachel Liew Ruo En; Afishah Alias (Enhanced Knowledge in Sciences and Technology, 2026)
Secure communication has become increasingly important with the proliferation of digital information exchange. To deliver a secure channel for data transmission, this study presents the design and implementation of a cryptographic framework using audio steganography in digital music. The purpose of this study is to ensure data confidentiality by combining cryptography and audio steganography techniques while preserving the perceptual quality of the modified audio signal. In this study’s encoder, plaintext encryption and ciphertext encoding are carried out using the symmetric Advanced Encryption Standard (AES) algorithm, phase coding, and Least Significant Bit (LSB) embedding. These processes result in a modified audio signal, referred to as the stego audio, which conceals the ciphertext without causing detectable distortion to the original audio signal. The stego audio is tramsmitted to the decoder, where decoding and decryption processes are subsequently carried out to retrieve the plaintext. To evaluate the security and effectiveness of the research framework, the Mean Squared Error (MSE), Peak Signal-to-Noise Ratio (PSNR), Bit Error Rate (BER), and Cepstral Distance (CD) were computed. Graphical visualisations, including a Mel-Frequency Cepstral Coefficient (MFCC) difference heatmap, were plotted to support the results. Experimental results demonstrated that the integration of AES encryption with phase coding and LSB embedding in digital music is effective in producing a stego audio with acceptable audio quality, capable of secure data transmission. This study showed that such an approach is aligned with the requirements of confidential data communication.